2022
DOI: 10.3390/genes13081357
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and Quality of Life of Healthy and Unilateral Diseased BRCA1/2 Pathogenic Variant Carriers after Risk-Reducing Mastectomy and Reconstruction Using the BREAST-Q Questionnaire

Abstract: Risk-reducing mastectomy (RRM) is the most efficient form of breast cancer (BC) risk reduction in BRCA1/2 pathogenic variant (pV) carriers. However, this intervention in physical integrity is associated with significant morbidity. We assessed long-term perception of satisfaction and health-related quality of life (QoL) after bilateral RRM and reconstruction using the validated BREAST-Q. We searched the prospective database of the Center for Hereditary Breast and Ovarian Cancer Cologne for previvors and survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Metcalfe 64 found better sexual well-being after nipple and areola-sparing RRM vs. skin-sparing RRM. However, another eight studies 49,62,63,[65][66][67][68]70 reported unchanged sexual function (pleasure/discomfort/habit) after RRM with reconstruction.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
See 2 more Smart Citations
“…Metcalfe 64 found better sexual well-being after nipple and areola-sparing RRM vs. skin-sparing RRM. However, another eight studies 49,62,63,[65][66][67][68]70 reported unchanged sexual function (pleasure/discomfort/habit) after RRM with reconstruction.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…The HRQoL including physical and mental components was unaffected in twelve studies 49, [56][57][58][59][60][61][62][63][64][65][66] and improved in one study 67 following RRM. Geiger 59 found similar long-term HRQoL in both high-risk women undergoing RRM and controls.…”
Section: Qol Outcomes After Rrm -Hrqolmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients also reported a strong desire to see photographs that would allow them to prepare for the final result. Satisfaction with the information obtained preoperatively appears to be directly related to satisfaction with the postoperative outcome, highlighting the importance of informed, shared decision-making around RRM [109].…”
Section: Psychological Outcomes Following Risk-reducing Mastectomymentioning
confidence: 99%
“…This BRCA1/2 positivity makes the affected susceptible to the risk of developing BC by 40–80%, making genetic testing even more crucial; because by offering bilateral risk‐reducing mastectomy (BRRM), this risk is reduced to ≥ 90% [9, 10]. Also, after PRRM, there is an improvement in BC‐specific survival, quality of life (QOL) and satisfaction rate in both BRCA1/2 carriers and patients [11, 12]. Previously, none of the centres in the country was offering genetic counselling and testing due to logistics constraints.…”
Section: Introductionmentioning
confidence: 99%